Role of Alkaloidal Precipitants for the Assay of Itraconazole in Capsules - Aruna Devi, P.; Mallikarjuna Rao, G.P.V.; Krishna Prasad, K.M.M.; Sastry, C.S.P. (Asian Journal of Chemistry, 2010)
Four simple spectrophotometric methods (A–D) for the assay of itraconazole (ICZ), based on its ability to form water-insoluble complexes, are described. These methods involve the quantitative precipitation of ICZ with phosphomolybdic acid (PMA, method A), ammonium molybdate (AM, method B), iodine (I2, method C) and tannic acid (TA, method D), followed by the second step of procedure, estimation of either released precipitant from the adduct (precipitate) through acetone addition (methods A, B or D) or the unreacted precipitant in the filtrate (method C) with the chromogenic reagents such as Co(II)-EDTA (for PMA), potassium thiocyanate (PTC, for AM), p-N-methyl aminophenol sulphate—sulphanilamide (PMAP-SA, for I2) and PMAP-Cr(VI) (for TA). These methods obey Beer's law and give reproducible results. The percentage recoveries are 99.67%.